Legal Implications of Restorative Justice in Narcotics Crimes: Integrating Accountability and Rehabilitation - Marquez, Neilpon Yulinar; Herman, KMS (al-Battar: Jurnal Pamungkas Hukum, 2025)
Drug crimes are a form of crime that has a systemic impact on public health, security, and order. The conventional criminal justice system, which tends to emphasize imprisonment, has not been fully effective in addressing the root causes of drug abuse, especially for users. In light of this, the restorative justice concept has surfaced as a substitute that seeks to rebuild the community, victims, and offenders via communication and rehabilitation. This study examines the legal implications of implementing restorative justice for drug crimes to realize restorative justice and rehabilitation for perpetrators. Law Number 35 of 2009 concerning Narcotics, Supreme Court Regulation Number 4 of 2010, Attorney General Regulation Number 15 of 2020, and Law Number 1 of 2023 concerning the Criminal Code are examined using a normative method. The study's findings suggest that restorative justice is only appropriate for drug users who fulfill specific requirements, such as not being recidivists and having a limited amount of evidence. The implementation of this approach has had a positive impact on reducing overcrowding in correctional institutions and fulfilling offenders' human rights to rehabilitation. However, obstacles remain, such as limited explicit regulations in the Narcotics Law and a lack of adequate rehabilitation facilities. Policy reform and strengthening synergy between law enforcement agencies are crucial steps in expanding the comprehensive implementation of restorative justice in the future.